PEMBERDAYAAN KELOMPOK NELAYAN MELALUI PROGRAM SENTRA KELAUTAN DAN PERIKANAN TERPADU DI DESA DALUM KECAMATAN SALIBABU KABUPATEN KEPULAUAN TALAUD - Juliati Prihatini; Preisy Celin Elungan; M. Rifai (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2022)
Dalum Village is one of the villages in the Talaud Islands Regency with its residents mostly living as fishermen, however, fishermen in Dalum Village are fishermen who are not fully empowered or have not been developed even though the government through the Fisheries Service of the Talaud Islands Regency has empowered fishermen groups in Dalum Village through the Integrated Marine and Fisheries Center Program. This study aims to describe and analyze the empowerment of fishermen groups through the Integrated Marine and Fisheries Center Program, inhibiting factors and supporting factors for the implementation of empowerment and efforts made in overcoming inhibiting factors. The design of this study is descriptive qualitative with an inductive approach. Data collection techniques are carried out through interviews, observations and documentation. Data analysis techniques are carried out by data reduction, data presentation and drawing conclusions. The results showed that the Empowerment of Fishermen Groups through the Integrated Marine and Fisheries Center Program in Dalum Village, Salibabu District, Talaud Islands Regency, Fishermen Group Study at the Teluk Lawasan Indah Cooperative conducted by the Fisheries Service of the Talaud Islands Regency was carried out with four indicators, namely human development, business development, environmental development and institutional development. Through these four indicators, the empowerment process has been running, but there are still many shortcomings that are obstacles in the implementation of empowerment such as: the low level of education of fishermen groups related to the technology used, the facilities and infrastructure used by fishermen groups are still simple, the dependence of fishermen groups on assistance provided by the government, and the lack of sufficient availability of electricity in the Island Regency area Talaud. Keywords: Fishing Group, Empowerment, Integrated Marine and Fisheries Center Program